Multimode‐Assisted Broadband Impedance‐Gradient Thin Metamaterial Absorber. Issue 10 (6th September 2022) - Wang, Yanzhao; Xu, He-Xiu; Wang, Chaohui; Luo, Huiling; Wang, Shaojie; Wang, Mingzhao
Abstract : Metamaterials have become a promising alternative for stealth technology due to their impressive abilities to freely manipulate electromagnetic waves. With the development of radar detection technology, stringent performances are required for metamaterial absorbers (MAs), such as wideband, wide‐angle operation, and thin thickness. Herein, a systematic strategy to achieve thin broadband MAs based on trilayer indium tin oxide (ITO) resistive films with multimodes is proposed. The operation mechanism and bandwidth enhancement are analyzed and discussed in terms of the equivalent circuit model and surface current distributions. Guided by the established impedance‐gradient theory, an absorber with high‐efficiency absorption is achieved. Numerical results show that it achieves operation bandwidth (reflection loss <−10 dB) ranging from 6.8 to 20.8 GHz and a fractional bandwidth of 101.4%. To demonstrate the applicability, a proof‐of‐concept sample is fabricated with a total thickness of only 3.5 mm, that is, 0.079  λ L at the lowest operating frequency. A good agreement of results between simulation and experiment has validated the effectiveness of our strategy, indicating broadband and large‐angle operation. It is believed that the research will stimulate the realization of wide‐angle broadband absorbers with thin thickness and further improve the application of stealth technology relying on absorption. Abstract : A multimode‐assisted strategy by involving impedance‐gradient theory is proposed to design broadband metamaterial absorbers (MA) based on indium tin oxide (ITO). The proposed absorber exhibits broadband absorption from 6.8 to 20.8 GHz and good angular performance under both transverse electric and transverse magnetic polarization. The entire thickness is only 3.5 mm, corresponding to 0.079  λ L at the lowest operating frequency.